The Role of Baitul Maal Wat Tamwil (BMT) in Community Economic Empowerment - Ramadhan, Al Insani Mutiara; Zaim, Muhammad; Hermawati, Sela; Sudirman, Wahyu Febri Ramadhan; Syaipudin, Muhammad (Global Sustainability Research Institute, 2025)
This study aims to examine the role of Baitul Maal wat Tamwil (BMT) in empowering the community's economy, especially in areas with low levels of economic welfare. BMT as a sharia-based microfinance institution has two main functions: a social fund management institution (Baitul Maal) and a commercial financial institution (Baitul Tamwil). This study uses a qualitative approach with a case study method on several BMTs in the research area. Data were collected through in-depth interviews, observations, and documentation, then analyzed using thematic analysis techniques. The study results indicate that BMT has contributed to improving the community's standard of living through micro-business financing, entrepreneurship training, and management of social funds in the form of zakat, infaq, and sedekah. In addition, BMT also plays a role in strengthening the community's social capital by encouraging active participation in community-based economic activities. The obstacles BMT faces in economic empowerment include limited capital, lack of financial literacy in the community, and challenges in maintaining sharia principles amidst competition from conventional financial institutions.